The effect of endometriosis on live birth rate and other reproductive outcomes in ART cycles: a cohort study - Muteshi, C; Ohuma, E; Child, T; Becker, C (Oxford University Press, 2018)
Study question: What is the effect of endometriosis compared to unexplained subfertility on live birth rate in women undergoing IVF and embryo transfer (ET)? Summary answer:Endometriosis decreases live birth rate in women undergoing IVF-ET treatment, particularly with increasing severity of the disease. What is known already:Endometriosis affects up to 50% of women seeking fertility treatment and is known to reduce fecundity. There remains a debate as to effects of endometriosis on the outcomes of IVF treatment, with live birth being a secondary outcome or not reported in most studies. Study design size duration:A retrospective cohort study analyzing data of IVF treatment cycles from January 2000 to December 2014 was carried out. Participants/materials setting methods:Women with endometriosis (n = 531) and women with unexplained subfertility (n = 737) undergoing a first cycle of IVF-ET in a tertiary fertility treatment center were included in the study. The primary outcome was live birth. Other outcome measures were response to ovarian stimulation, embryo development and implantation rate. Bivariate and multivariate logistic regression analysis was performed and differences compared using Chi squared test of Student's t-test as appropriate. Main results and the role of chance:Women with endometriosis had 24% less likelihood of a live birth when compared to those with unexplained subfertility [odds ratio (OR) 0.76 (95% CI, 0.59-0.98) P = 0.035]. This effect became more apparent with increasing severity of endometriosis. Using multivariable logistic regression analysis, the trend for lower live birth rate remained but did not reach statistical significance [adjusted OR 0.76 (95% CI 0.56-1.03), P = 0.078]. Women with endometriosis were as likely as those with unexplained subfertility to have a singleton live birth when two embryos were transferred as opposed to a single ET [OR 1.38 (95% CI 0.73-2.62), P = 0.32 and OR 3.22 (95% CI 1.7-6.05), P = 0.0003, respectively]. Compared to women with unexplained subfertility, those with endometriosis had fewer oocytes retrieved [(10.54 (95% CI 10.13-0.95) and 9.15 (95% CI 8.69-9.6), respectively], lower blastocyst transfer [OR 0.24 (95% CI 0.12-0.5), P = 0.0001] and a significantly reduced implantation rate [OR 0.73 (0.58-0.92), P = 0.007]. Limitations reasons for caution:The study is limited by a retrospective design. By limiting the study to a single ET cycle, it was not possible to assess the cumulative outcome including use of all frozen embryos. Wider implications of the findings:Endometriosis has similar phenotypes among women in different populations and would be expected to have a similar effect on fertility. These results are therefore generalizable to other populations of women. Study funding/competing interests:None. Trial registration number:Not applicable.